Genetic resources for future - Singh, B.; Singh, M.; N. Rai, H. Lal.; Bhardwaj, D. R.; Kumar, Rajesh; Prasanna, H. C.; Sanwal, S. K.; Chaubey, T.; Pandey, S.; Ranjan, J. K.; Tewari, S. K.; Singh, B. K.; et al. (Indian Horticulture, 2019)
The IIVR, Varanasi is the national active germplasm centre for vegetable crops in India. It facilitates multiplication, conservation and evaluation of vegetable germplasm in collaboration with NBPGR, New Delhi. A total of 6,596 accessions of 31 different major and minor vegetable crops are being maintained at ICAR-IIVR, Varanasi. The institute is also maintaining 465 accessions of 60 related wild species of ten vegetable crops.